2017
DOI: 10.1128/aac.00739-17
|View full text |Cite
|
Sign up to set email alerts
|

The Myxobacterial Metabolite Soraphen A Inhibits HIV-1 by Reducing Virus Production and Altering Virion Composition

Abstract: Soraphen A is a myxobacterial metabolite that blocks the acetyl-coenzyme A carboxylase of the host and was previously identified as a novel HIV inhibitor. Here, we report that soraphen A acts by reducing virus production and altering the gp120 virion content, impacting entry capacity and infectivity. These effects are partially reversed by addition of palmitic acid, suggesting that inhibition of HIV envelope palmitoylation is one of the mechanisms of antiviral action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As such, blocking lipogenesis has emerged as a potential antiviral therapeutic option. For instance, lipogenesis inhibitors have been demonstrated to block the infection of hepatitis C virus 286 , HIV 287 , West Nile virus 288 , rotavirus 289 , Epstein-Barr virus 290 , dengue virus 291 , Japanese encephalitis virus 291 and chikungunya virus 291 . Lipogenesis inhibitors could also potentially be beneficial against the COVID-19 pandemic, as like all viruses, SARS-CoV-2 relies on newly synthesized phospholipids for its replication 292 .…”
Section: Box 2 | Emerging Applications Of Lipogenesis Inhibitorsmentioning
confidence: 99%
“…As such, blocking lipogenesis has emerged as a potential antiviral therapeutic option. For instance, lipogenesis inhibitors have been demonstrated to block the infection of hepatitis C virus 286 , HIV 287 , West Nile virus 288 , rotavirus 289 , Epstein-Barr virus 290 , dengue virus 291 , Japanese encephalitis virus 291 and chikungunya virus 291 . Lipogenesis inhibitors could also potentially be beneficial against the COVID-19 pandemic, as like all viruses, SARS-CoV-2 relies on newly synthesized phospholipids for its replication 292 .…”
Section: Box 2 | Emerging Applications Of Lipogenesis Inhibitorsmentioning
confidence: 99%
“…As SorA-specific data, we chose the experimental EC 50 value of 4.7 nM for the modeling, as it was slightly higher than the one with wild-type DENV. The information that SorA acts on the viral production, but neither on the release nor on the entry process of viral particles into the cells, based on mechanistic data for HCV and HIV, , was later incorporated into a combined equation for viral release, infection and production. Although DENV enters the human body through a mosquito bite, the virus is directly injected into the system in our models.…”
Section: Resultsmentioning
confidence: 99%
“…Soraphen A (SorA), a macrolide natural product produced by the myxobacterium Sorangium cellulosum , has been recently shown to have anticancer, immune-modulatory, and antiviral activities. SorA is a potent inhibitor of acetyl-CoA carboxylase (ACC), thereby interfering with fatty acid metabolism. The validity of ACC inhibition as a host-directed antiviral target has been shown with SorA in cellular models of hepatitis C virus (HCV) and human immunodeficiency virus (HIV). Synthetic inhibitors of the catalytic site of ACC have been recently shown to inhibit Flaviviridae like DENV, West Nile virus, or Zika virus in cellular models with low micromolar potency. , As SorA exerts a superior inhibitory potency against ACC, we probed its efficacy against DENV in this study. In order to assess the potential of SorA beyond a tool compound as a drug, we report the in vitro absorption, distribution, metabolism, and excretion (ADME) properties and the in vivo pharmacokinetic (PK) studies, followed by its efficacy in a DENV animal infection model.…”
mentioning
confidence: 99%
“…SorA inhibits formation of the "membranous web", a cellular structure that is generated during and serves as a platform for replication of RNA viruses. Studies showed that SorA inhibits replication of hepatitis C virus (HCV), human immunodeficiency virus (HIV), and DENV (Koutsoudakis et al, 2015;Fleta-Soriano et al, 2017). A second natural product shown to have broad antiviral activity was the lantibiotic peptide labyrinthopeptin A1 (LabyA1; Férir et al, 2013).…”
Section: Alphaviruses (Chikungunya): Molecular Biology Pathogenesismentioning
confidence: 99%